2020
DOI: 10.1186/s40494-020-00365-4
|View full text |Cite
|
Sign up to set email alerts
|

Copper exposure in medieval and post-medieval Denmark and northern Germany: its relationship to residence location and social position

Abstract: For medieval and post-medieval Denmark and northern Germany, trace elements can potentially contribute to our understanding of diet, migration, social status, exposure to urban settings, and disease treatment. Copper, of particular interest as a marker of access to everyday metal items, can be used to clarify socioeconomic distinctions between and within communities. Postmortem alteration of bone (diagenesis), however, must be ruled out before the elements can be used to characterize life in the past. Femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 92 publications
4
22
0
Order By: Relevance
“…In Ribe X1029/KLR-10831, all concentration values are higher than those in the unburied samples, especially for Mn but also Fe and Ba. Copper and Pb are higher than in the non-interred individuals, but they are within the range of archaeological Danish skeletons reported elsewhere [37]. The Spearman correlation matrix shows that in X1256/KLR-10810 there are strong correlations between Sr and Ba (r = 0.94), as well as Cu and Pb (r = 0.79) (Additional file 2).…”
Section: Archaeological Samples From Ribe Denmarksupporting
confidence: 76%
See 2 more Smart Citations
“…In Ribe X1029/KLR-10831, all concentration values are higher than those in the unburied samples, especially for Mn but also Fe and Ba. Copper and Pb are higher than in the non-interred individuals, but they are within the range of archaeological Danish skeletons reported elsewhere [37]. The Spearman correlation matrix shows that in X1256/KLR-10810 there are strong correlations between Sr and Ba (r = 0.94), as well as Cu and Pb (r = 0.79) (Additional file 2).…”
Section: Archaeological Samples From Ribe Denmarksupporting
confidence: 76%
“…Previous work has shown that there is an explicable pattern in Cu and Pb concentrations in bulk bone samples from medieval to post-medieval skeletons interred in cemeteries in Denmark and northern Germany [37,52]. The distribution of these elements among the different bone microstructural elements is perhaps the strongest reason to believe a biogenetic signal is retained that is not masked by diagenetic processes [1].…”
Section: Diagenesismentioning
confidence: 96%
See 1 more Smart Citation
“…Copper concentrations in archaeological bones have been used as a palaeodietary indicator to identify a diet rich in meat [85][86][87], but the relationship between Cuuptake and dietary composition is still unclear [88,89]. The impact of Cu-exposure on medieval and post-medieval populations through the use of kitchen utensils and environmental factors have been investigated and it has been argued that the Cu concentrations in bones indicate either a higher social class or a higher degree of urbanisation (see [90] and references therein).…”
Section: Coppermentioning
confidence: 99%
“…Lead was used throughout medieval Europe for glazing ceramics; a glaze which could release Pb 2+ ions into the foodstuff if the food had a low pH. Copper was utilised in the medieval period and post-modern time as a very abundant material for large cooking pots and food containers in wealthy homes [90]. The estimated time-period for the burials in both chapels are 17th to 18th century, where the use of Cu utensils is expected to have been widespread in large parts of both societies.…”
Section: Lead and Coppermentioning
confidence: 99%